Authoritarian Leadership and Employee Job Performance: A Moderated Mediation of Job Role Clarity, Trust in Leaders and Power Distance - Edilpatriz Edilpatriz; Syahrizal; Tika Rahma Yani Siregar (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Leadership is a critical factor in determining organizational success. It serves as the primary catalyst for significant changes within an organization, where leadership is defined as the art of fostering organizational alignment and stability. Purpose: This study examines the direct effect of authoritarian leadership on employee job performance. Furthermore, this study explores the moderating role of power distance and the mediating roles of job role clarity and trust in leaders.Design/methodology/approach: This study employs a quantitative survey-based design with a sample of 176 employees from water utility company in West Sumatra. The data were analyzed using structural equation modeling with partial least squares (SEM PLS).Findings/Results: The research findings show that authoritarian leadership has a negative effect on employee job performance. Furthermore, the results indicate that power distance moderates the relationship between authoritarian leadership and both job role clarity and employee job performance. The findings also reveal that job role clarity and trust in leaders mediate the effect of authoritarian leadership on employee job performance.Conclusion: The authoritarian leadership style has a negative influence on the work performance of employees at a water utility company in West Sumatera, resulting in an unhealthy impact on the company's performance.Originality/value (state of the art): This research combines the mediating influence of job role clarity and trust in leaders for the influence of authoritarian leadership on employee job performance, and the moderating effect of power distance on the influence of authoritarian leadership on job role clarity and employee job performance. Keywords: authoritarian leadership, employee job performance, job role clarity, power distance, trust in leaders